Resveratrol, a natural antioxidant, protects monosodium iodoacetate-induced osteoarthritic pain in rats - Wang, Zhu-Min; Chen, Yong-Cai; Wang, Da-Peng (Biomedicine & pharmacotherapy, 2016)
Osteoarthritis (OA) is a chronic progressive joint disease characterized by advanced joint pain, subchondral bone sclerosis and articular cartilage degeneration. Resveratrol has been shown to have anti-inflammatory, cardioprotective and antioxidant properties and to inhibit platelet aggregation and coagulation. However, the effects of resveratrol on OA have not been examined. In this study, we investigate the protective effects of resveratrol on monosodium iodoacetate (MIA)-induced OA through inhibition of cyclooxygenase (COX-2) and inducible nitric oxide synthase (iNOS) signaling pathway in a rat model. A single intra-articular injection of MIA was injected into rats for the induction of OA. The mechanical, heat and cold hyperalgesia were measured at days 0, 7 and 14. The serum and synovial fluid levels of IL-1β, IL-10 and TNF-α and osteocalcin were measured by enzyme-linked immunosorbent assay. The mRNA and protein expressions of IL-1β, IL-10, TNF-α, Il-6, MMP-13 and COX-2 and iNOS were determined by RT-PCR and western blot, respectively. Osteoarthritic lesion in the knee joint was evaluated by histological analysis. MIA-injected rats treated with resveratrol at a dose of either 5 or 10mg/kg body weight were significantly reduced hyperalgesia of mechanical, heat and cold and increased the vertical and horizontal movements. Subsequently, MIA-injected rats increased serum and synovial fluid levels of IL-1β, IL-10, IL-6, TNF-α, MMP-13 and osteoclastic activity marker, osteocalcin and its articular cartilage mRNA and protein expressions. Further, MIA-injected rats increased COX-2 and iNOS mRNA and protein expressions were decreased by resveratrol. The protective effect of resveratrol was comparable to a reference drug, etoricoxib. The cartilage damage induced by MIA were attenuated by resveratrol. Taken together, resveratrol has the potential to improve MIA-induced cartilage damage by inhibiting the levels and expressions of inflammatory mediators suggesting that resveratrol may be a potential therapeutic agent for OA.